A Human Pharmacological Study Comparing Conventional Heparin and a Low Molecular Weight Heparin Fragment - Bratt, G; Törnebohm, E; Lockner, D; Bergströ, G (Thrombosis and Haemostasis, 1985)
The pharmacokinetics of a heparin fragment of low molecular weight (LMWH) of 4000-5000 D and unfractioned standard heparin (UFH) have been studied after i. v. injections of different doses and infusions in 8 humans.The heparin activity was significantly higher and the effect on APTT lower after LMWH fragment as compared to UFH in the same doses.The half-life of heparin activity was about 1 hr for UFH and about 2 hr for LMWH. LMWH was found to be eliminated according to first order kinetics and there were no signs of dose dependency.
Keywords: Heparin; Low molecular weight heparin; Pharmacokinetics; Humans